Population based time trends and socioeconomic variation in use of radiotherapy and radical surgery for prostate cancer in a UK region: continuous survey. (22nd April 2010) - Lyratzopoulos, Georgios; Barbiere, Josephine M; Greenberg, David C; Wright, Karen A; Neal, David E
Abstract : Objective To examine variation in the management of prostate cancer in patients with different socioeconomic status. Design Survey using UK regional cancer registry data. Setting Regional population based cancer registry. Participants 35 171 patients aged ≥51 with a diagnosis of prostate cancer, 1995-2006. Main outcome measures Use of radiotherapy and radical surgery. Socioeconomic status according to fifths of small area deprivation index. Results Over the nine years of the study, information on stage at diagnosis was available for 15 916 of 27 970 patients (57%). During the study period, the proportion of patients treated with radiotherapy remained at about 25%, while use of radical surgery increased significantly (from 2.9% (212/7201) during 1995-7 to 8.4% (854/10 211) during 2004-6, P<0.001). Both treatments were more commonly used in least deprived compared with most deprived patients (28.5% v 21.0% for radiotherapy and 8.4% v 4.0% for surgery). In multivariable analysis, increasing deprivation remained strongly associated with lower odds of radiotherapy or surgery (odds ratio 0.92 (95% confidence interval 0.90 to 0.94), P<0.001, and 0.91 (0.87 to 0.94), P<0.001, respectively, per incremental deprivation group). There were consistently concordant findings with multilevel models for clustering of observations by hospital of diagnosis, with restriction of the analysis to patients with information on stage, and with sequential restriction of the analysis to different age, stage, diagnosis period, and morphology groups. Conclusions After a diagnosis of prostate cancer, men from lower socioeconomic groups were substantially less likely to be treated with radical surgery or radiotherapy. The causes and impact on survival of such differences remain uncertain.